2022
DOI: 10.47363/jaicc/2022(1)107
|View full text |Cite
|
Sign up to set email alerts
|

Artificial Intelligence in Healthcare and Biotechnology: A Review of the Saudi Experience

Abstract: Whether in analyzing laboratory and imaging results, devising vaccination plans in a pandemic, or predicting patient prognosis, artificial intelligence [AI] was shown to be an indispensable tool in the field of healthcare. Saudi Arabia is no stranger to the many benefits of AI in medicine. In this paper, we expand on the past, ongoing, and future applications of AI in the Saudi healthcare sector.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…The successful use of AI in healthcare depends on the awareness and perception of medical experts of its applications. 22 To the best of our knowledge, this is one of the few studies in the GCC countries 23 to evaluate the opinions and attitudes of physicians and medical students on AI medical applications. Overall, we found that both physicians and medical students across all specialties and years of experience have a positive perspective about the future use of AI in healthcare which is similar to the previously reported attitude.…”
Section: Discussionmentioning
confidence: 99%
“…The successful use of AI in healthcare depends on the awareness and perception of medical experts of its applications. 22 To the best of our knowledge, this is one of the few studies in the GCC countries 23 to evaluate the opinions and attitudes of physicians and medical students on AI medical applications. Overall, we found that both physicians and medical students across all specialties and years of experience have a positive perspective about the future use of AI in healthcare which is similar to the previously reported attitude.…”
Section: Discussionmentioning
confidence: 99%